2015
DOI: 10.1051/0004-6361/201425451
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cosmic rays on extrasolar Earth-like planets

Abstract: Context. Theoretical arguments indicate that close-in terrestial exoplanets may have weak magnetic fields, especially in the case of planets more massive than Earth (super-Earths). Planetary magnetic fields, however, constitute one of the shielding layers that protect the planet against cosmic-ray particles. In particular, a weak magnetic field results in a high flux of Galactic cosmic rays that extends to the top of the planetary atmosphere. Aims. We wish to quantify the flux of Galactic cosmic rays to an exo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 101 publications
(195 reference statements)
1
54
2
Order By: Relevance
“…Segura et al (2010) have modelled the photochemical effects of a large UV flare observed on AD Leonis (AD Leo), and find that UV surface fluxes stay within non-lethal dosages. Grießmeier et al (2015b) find that GCR-induced O 3 destruction results in up to 40% increased biologically weighted UV surface flux. However, as the AD Leo spectrum used features lower UV-A and UV-B fluxes and the planetary atmosphere retains enough O 3 to shield from UV-C, total UV fluxes are much lower than on Earth.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Segura et al (2010) have modelled the photochemical effects of a large UV flare observed on AD Leonis (AD Leo), and find that UV surface fluxes stay within non-lethal dosages. Grießmeier et al (2015b) find that GCR-induced O 3 destruction results in up to 40% increased biologically weighted UV surface flux. However, as the AD Leo spectrum used features lower UV-A and UV-B fluxes and the planetary atmosphere retains enough O 3 to shield from UV-C, total UV fluxes are much lower than on Earth.…”
Section: Introductionmentioning
confidence: 80%
“…Grenfell et al (2007a) investigated the effect of GCRs on biomarker molecules for biogenic Earth-like planets surrounding an active M-dwarf with varying heliospheric and planetary magnetic shielding. This study was recently built on by Grießmeier et al (2015b) and Grießmeier et al (2015a), who use the updated version of the CR model presented in the current work to examine the effect of the planetary magnetospheric shielding on GCR-induced photochemistry. With a maximum of 20% difference in column-integrated ozone values (and 6% for CH 4 and H 2 O) between no magnetic shielding and ten times the Earth's magnetic field strength, they find GCRs have nearly no effect on the resulting planetary spectra.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NASA found that there is a purple light, which is created by nitric oxide, and on Mars it produces its own light [47][48][49][50].…”
Section: The Effect Of the Rays And Colors Of External Factors On Thementioning
confidence: 99%
“…On the other hand, the correct description of the transport of cosmic rays in other astrophysical systems is also of great interest. For example, in astrospheres, i.e., circumstellar regions occupied by stellar winds, it is of high relevance in the context of exoplanet research (e.g., Scalo et al 2007;Grenell et al 2012;Grießmeier et al 2015) and potentially for an understanding of cosmic-ray anisotropy at high energy (Scherer et al 2015). Another example is the, at least partly diffusive, cosmic-ray transport in galactic halos (e.g., Heesen et al 2009;Mao et al 2015).…”
Section: Introductionmentioning
confidence: 99%